Winter wheat yield depending on the use of biological, chemical factors and renewable bioresources when reducing intensity of soil treatment - N. I. Devterova; O. A. Blagopolychnaya (Новые технологии, 2018)
The influence of straw embedding of grain crops in various ways in combination with doses of mineral fertilizers on the yield of winter wheat and the main indicators of soil fertility have been studied. It’s been revealed that the use of renewable bioresources in the form of straw does not provide a significant effect on winter wheat yields in the first year of research. The highest yield level was obtained in the variants according to the background: 59.5 centners per hectare and 53.5 centners per hectare in both methods of treatment.